Pengaruh perbedaan sistem pembagian kerja terhadap kelelahan penata anestesi di ruang operasi di indonesia : The effects of differences in the divison of labor on fatigue of nurse anesthetists in operating rooms in indonesia - yusniawati, Yustina Ni Putu; Lewar, Emanuel Ileatan; Putra, I Gde Agus Shuarsedana (Stikes Wira Medika Bali, 2021)
The division of labor in this study refers to the working hour arrangement made by the hospital management for 24-hour optimal service. Nurses in the operating room as health workers need the division of labor. It considers that not all planned or scheduled surgery can be carried out at a predetermined time since delays, acceleration, or cancellation can occur. Nurses in the operating room must be ready for 24 hours for surgeries. However, an intensive division of labor with long working hours is an essential factor affecting the fatigue levels of nurse anesthetists in the operating room. Fatigue decreases alertness, concentration, judgment, and mood. To determine the effect of different divisions of labor over fatigue levels of nurse anesthetists in the operating room in Indonesia. This study used a quantitative research design with an analytical observational design and a cross-sectional approach. The sampling technique was purposive sampling with a sample of 228 nurse anesthetists in the operating room from hospitals in various regions throughout Indonesia. Data was collected with OFER and ENSS questionnaires translated into Indonesian and tested previously for validity and reliability. Data were analyzed using SPSS Version 20, with univariate analysis. It indicates that the respondents were primarily male, aged 22 to 68 years old, married, had an associate’s degree, with >3 years tenure, the number of operating rooms were between 1 to 26 rooms, the number of nurse anesthetists ranges from 1 to 43 people, and the number of surgery ranges from 1 to 50 per day. Bivariate analysis was carried out using Kruskal-Wallis analysis. The results showed a difference between work shifts and work fatigue, where 12 hours-12 hours work shift have severe fatigue rates than others. The work shifts regulate the working hours of nurse anesthetists to work optimally. It is essential to adjust the work shift so that they can have enough time to rest. An irregular division of work hours and the work hours longer than the rest duration are significant factors causing chronic fatigue in nurse anesthetists.